Amlodipine induced bullous pemphigoid: a case report - Guddeti, Likhitha; Nikhat P., Yashmeen; Reddy, G. Sai Kumar; Mokkatla, Pavithra (International Journal of Research in Medical Sciences, 2025)
Bullous pemphigoid (BP) is a common autoimmune blistering disease primarily affecting the elderly. It is often associated with itchy urticarial plaques and can be identified by the production of subepidermal blisters. Autoantibodies that target the proteins BP180 and BP230, which appear at the dermo-epidermal junction, formed as part of the pathogenesis. However, the exact reason for occurrence of this disease is still unknown, some drugs, such as antihypertensives like calcium channel blockers (CCBs), have been associated to the occurrence or aggravation of elevated blood pressure. The patient in this case study is a 65-year-old woman who was prescribed with amlodipine, a drug commonly prescribed to treat hypertension, for several years before developing BP-like lesions. The patient developed lesions on the face, chest, belly, and trunk; histological and clinical results supported the BP diagnosis. The patient’s symptoms improved after stopping amlodipine and modifying her treatment plan. This case highlights the need for more cautious when prescribing medications to elderly patients, particularly those with comorbidities, who are at higher risk for drug-induced autoimmune conditions. When a patient presents with new-onset bullous lesions, particularly in the context of recent medication changes, the possibility of drug-induced BP (DIBP) should be considered.